Notes on the names of the Tetrastigma (Vitaceae) hosts of Rafflesia (Rafflesiaceae) - Veldkamp, Jeff F. (Research Center for Biology, 2009)
Older epithets for Tetrastigma rafflesiae Miq. (1863; Vitaceae), also known as T. lanceo- larium auct. non Planch. and T. leucostaphylum auct. non Alston ex Mabb. (Vitaceae), are provided by Cissus coriacea DC. (1824) and Cissus verrucosa Steud. (1840), whereby the correct name for this host of Rafflesia spp. must be Tet- rastigma coriaceum (DC.) Gagnep. The name Tetrastigma pisicarpum (Miq., 1863) Planch., host of at least Rafflesia patma, likewise must be replaced by Tetrastigma scariosum (Blume, 1825) Planch.